Induction of a mitogen-responsive gene after expression of the Ha-ras oncogene in NIH 3T3 fibroblasts. - Werenskiold, A K (1989)
A cDNA clone, T1, has been isolated whose corresponding mRNA was transiently expressed at highly elevated levels after conditional expression of the Ha-ras(EJ) gene and after mitogenic activation of quiescent NIH 3T3 cells. Glucocorticoid hormone stimulated substantial T1 expression as well but only in proliferating cells. At least two different signaling pathways participate in the regulation of the T1 gene: a protein kinase C-dependent signal is involved in the response of proliferating NIH 3T3 cells to glucocorticoid in the absence but not the presence of p21ras, whereas a protein kinase C-independent mechanism mediates the response to serum factors. Treatment of cells with the protein kinase inhibitor 2-aminopurine blocked induction of expression of the T1 gene. T1 mRNA accumulation is regulated at the transcriptional level.